2014
DOI: 10.1182/blood-2013-10-535831
|View full text |Cite
|
Sign up to set email alerts
|

STXBP1 promotes Weibel-Palade body exocytosis through its interaction with the Rab27A effector Slp4-a

Abstract: Key Points• Recruitment of STXBP1 by Slp4-a promotes WeibelPalade body exocytosis.• Ex vivo EIEE4 endothelial cells haploinsufficient for STXBP1 have impaired Weibel-Palade body exocytosis.Vascular endothelial cells contain unique rod-shaped secretory organelles, called WeibelPalade bodies (WPBs), which contain the hemostatic protein von Willebrand factor (VWF) and a cocktail of angiogenic and inflammatory mediators. We have shown that the Rab27A effector synaptotagmin-like protein 4-a (Slp4-a) plays a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 61 publications
5
58
0
2
Order By: Relevance
“…Cord blood was collected from umbilical veins within 48 hours after delivery and was processed for BOEC isolation essentially as described before . cbBOECs were cultured in EC growth medium (EGM)‐2 (Lonza, Basel, Switzerland, CC‐3162) supplemented with 18% fetal calf serum (EGM‐18; Bodinco, Alkmaar, The Netherlands) . Human embryonic kidney 293T (HEK293T) cells were cultured in Gibco Dulbecco's Modified Eagle Medium, high glucose, pyruvate (ThermoFisher, Landsmeer, The Netherlands) for regular passing and seeding and in EGM‐18 for virus production.…”
Section: Methodsmentioning
confidence: 99%
“…Cord blood was collected from umbilical veins within 48 hours after delivery and was processed for BOEC isolation essentially as described before . cbBOECs were cultured in EC growth medium (EGM)‐2 (Lonza, Basel, Switzerland, CC‐3162) supplemented with 18% fetal calf serum (EGM‐18; Bodinco, Alkmaar, The Netherlands) . Human embryonic kidney 293T (HEK293T) cells were cultured in Gibco Dulbecco's Modified Eagle Medium, high glucose, pyruvate (ThermoFisher, Landsmeer, The Netherlands) for regular passing and seeding and in EGM‐18 for virus production.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Bierings et al reported the Rab27A effector synaptotagmin-like protein 4-a (Slp4-a) plays a critical role in regulating hormone-evoked WPB exocytosis [42]. Using a nonbiased proteomic screen for targets of Slp4-a, they identify syntaxin-binding protein 1 (STXBP1) and syntaxin-2 and -3 as endogenous Slp4-a binding partners in endothelial cells [43]. Applying co-immunoprecipitations and siRNA techniques, analysis of isolated blood outgrowth endothelial cells from patient carrying mutation in STXBP1, they demonstrate that the Rab27A-Slp4-a complex on WPB promotes exocytosis through an interaction with STXBP1 [43].…”
Section: Regulation Of Vwf Protein Secretionmentioning
confidence: 99%
“…Using a nonbiased proteomic screen for targets of Slp4-a, they identify syntaxin-binding protein 1 (STXBP1) and syntaxin-2 and -3 as endogenous Slp4-a binding partners in endothelial cells [43]. Applying co-immunoprecipitations and siRNA techniques, analysis of isolated blood outgrowth endothelial cells from patient carrying mutation in STXBP1, they demonstrate that the Rab27A-Slp4-a complex on WPB promotes exocytosis through an interaction with STXBP1 [43]. Interestingly, STXBP5 has also been shown to differentially regulate exocytosis in endothelial cells and platelets [44, 45].…”
Section: Regulation Of Vwf Protein Secretionmentioning
confidence: 99%
“…, 2011a; van Breevoort et al. , 2012, 2014). However, it is unknown how the cortically anchored WPBs are transferred to the fusion-mediating SNARE machinery after secretagogue stimulation and whether a plasma membrane–tethered WPB intermediate is formed in the course of acute WPB exocytosis.…”
Section: Introductionmentioning
confidence: 99%